DEVELOPING A PICTURE BOOK OF LOCAL FOLKTALES TO FACILITATE READING LITERACY FOR THE 8TH GRADE STUDENTS OF SMP ANAK NEGERI SANGGAU - Evander Fraseda; Endang Susilawati; Ikhsanudin Ikhsanudin; Eusabinus Bunau; Surmiyati Surmiyati (Journal of English Educational Study (JEES), 2022)
This study aimed to develop local folktales content for junior high school students based on local folktales from the Sanggau regency. To achieve the aim, this research was done by focusing on knowing what kind of a picture book was developed, how a picture book was done, and how appropriate the product was. The book was to facilitate class VIII students in reading literacy programs. This research used Design and Development by Branch. There were 20 students in the eighth grade and an English teacher of SMP Anak Negeri Sanggau as the objects. Design and development based on ADDIE consist of analysis, design, and development. The data collection of this research was done through interviews, questionnaires, and documentation. The findings of this study revealed the needs analysis at the student level, product needs, product topics, and product design. Thus, it was found that the product was appropriate for the students through the validations.